Diaphragm Used with Replens Gel and Risk of Bacterial Vaginosis: Results from a Randomized Controlled Trial - Craig R. Cohen; Su-Chun Cheng; Stephen Shiboski; Tsungai Chipato; Martin Matu; James Mwangi; Monalisa E. S. Mutimutema; Jennifer Tuveson; Mavis Kamba; Nancy Padian; Ariane van der Straten (Hindawi Limited, 2012)
Background. Bacterial vaginosis (BV) has been linked to female HIV acquisition and transmission. We investigated the effect of providing a latex diaphragm with Replens and condoms compared to condom only on BV prevalence among participants enrolled in an HIV prevention trial. Methods. We enrolled HIV-seronegative women and obtained a vaginal swab for diagnosis of BV using Nugent's criteria; women with BV (score 7-10) were compared to those with intermediate (score 4-6) and normal flora (score 0-3). During quarterly follow-up visits over 12-24 months a vaginal Gram stain was obtained. The primary outcome was serial point prevalence of BV during followup. Results. 528 participants were enrolled; 213 (40%) had BV at enrollment. Overall, BV prevalence declined after enrollment in women with BV at baseline (OR=0.4, 95% CI 0.29-.56) but did not differ by intervention group. In the intention-to-treat analysis BV prevalence did not differ between the intervention and control groups for women who had BV (OR=1.01, 95% CI 0.52-1.94) or for those who did not have BV (OR=1.21, 95% CI 0.65-2.27) at enrollment. Only 2.1% of participants were treated for symptomatic BV and few women (5-16%) were reported using anything else but water to cleanse the vagina over the course of the trial. Conclusions. Provision of the diaphragm, Replens, and condoms did not change the risk of BV in comparison to the provision of condoms alone.